Mrs. Hippo's Pizza Parlour - French, Vivian; Scruton, Clive (London : Kingfisher, 2004)
Business is bad at Mrs. Hippo's Pizza Parlour until her son William has a brilliant idea.
2.5
K-3
Keywords: Animals -- Fiction; Hippopotamus -- Fiction; Pizza -- Fiction; Hippopotamuses -- Fiction